Pemberdayaan Masyarakat melalui Edukasi dan Pengawasan Investasi Bodong di Lingkungan Masyarakat Desa Cipatujah - Sudiarti, Sri; Pekerti, Retno Dyah; Khodijah, Amalia Siti; Syfa, Raisa Hillia Aini (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
Community service aims to provide education so that the public is wiser in choosing investments, avoiding the trap of fraudulent investments. The methods used are seminars and talk shows. The expected results include increasing public awareness of the dangers of fraudulent investments, reducing fraud cases, collaboration between the government and financial institutions, and consumer protection. Positive impacts on shared prosperity can be achieved through financial transparency and strict supervision, allowing the public to invest safely and confidently. This protects against financial losses and increases trust in the financial system, which contributes to economic stability and justice. In conclusion, financial transparency, socialization, and supervision are the three main pillars in protecting the public from fraudulent investments, ensuring a safe and trusted investment environment